Doxorubicin-induced senescence promotes resistance to cell death by modulating genes associated with apoptotic and necrotic pathways in prostate cancer DU145 CD133+/CD44+cells - Tatar, Cansu; Avci, Cigir Biray; Acikgoz, Eda; Oktem, Gulperi (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2023)
Cancer stem cells (CSCs) are the most important cause of cancer treatment failure. Traditional cancer treatments, such as chemotherapy and radiotherapy, damage healthy cells alongside malignant cells, leading to severe adverse effects. Therefore, inducing cellular senescence without triggering apoptosis, which further damages healthy cells, may be an alternative strategy. However, there is insufficient knowledge regarding senescence induction in CSCs that show resistance to treatment and stemness properties. The present study aims to elucidate the effects of senescence induction on proliferation, cell cycle, and apoptosis in prostate CSCs and non-CSCs. Prostate CSCs were isolated from DU145 cancer cells using the FACS method. Subsequently, senescence induction was performed in RWPE-1, DU145, prostate CSCs, and non-CSCs by using different concentrations of Doxorubicin (DOX). Cellular senescence was detected using the senescence markers SA-beta-gal, Ki67, and senescence-associated heterochromatin foci (SAHF). The effects of senescence on cell cycle and apoptosis were evaluated using the Muse Cell Analyzer, and genes in signaling pathways associated with the apoptotic/necrotic pathway were analyzed by real-time PCR. Prostate CSCs were isolated with 95.6 +/- 1.4% purity according to CD133+/CD44+ characteristics, and spheroid formation belonging to stem cells was observed. After DOXinduced senescence, we observed morphological changes, SA-beta-gal positivity, SAHF, and the lack of Ki67 in senescent cells. Furthermore; we detected G2/M cell cycle arrest and downregulation of various apoptosis-related genes in senescent prostate CSCs. Our results showed that DOX is a potent inducer of senescence for prostate CSCs, inhibits proliferation by arresting the cell cycle, and senescent prostate CSCs develop resistance to apoptosis.
Keywords: Senescence; Prostate cancer; Cancer stem cell; Therapy-induced senescence; Doxorubicin; Cell cycle arrest; STEM-CELLS; IDENTIFICATION; HETEROGENEITY; CHEMOTHERAPY; Biochemistry & Molecular Biology; Biophysics